PENGARUH MODEL PEMBELAJARAN PROBLEM SOLVING BERBANTUAN MIND MAPPING TERHADAP PEMAHAMAN KONSEP SISWA KELAS IV - Janah, Sifaul; Suryani, Ela (JISPE Journal of Islamic Primary Education, 2022)
ABSTRACT The purpose of this study was to determine the effect of mind mapping-assisted problem solving learning model on the understanding of energy concepts in fourth grade students of SDN 02 Sukorejo. This study uses a quantitative approach, experimental method with Non-Equivalent Control Group Design. The results showed that there was an average difference in students' conceptual understanding ability between the control class and the experimental class, which was seen from the t count > t table = 2,440 > 2,009 with a sig. (2-tailed) is 0.018 where this value is <0.05, then Ho is rejected and Ha is accepted. There is an effect of mind mapping-assisted problem solving learning model on students' conceptual understanding, seen from F count = 6.099 with a significance level of 0.021 < 0.05, the results of the regression test value R2 = 0.212 = 21.2%, then this regression model can affect the participation variable. So it can be concluded that there is an influence between the problem solving learning model assisted mind mapping on the understanding concepts class IV.